Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 309551 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "TaxonKey is Anser fabalis (Latham, 1787)" ] } The dataset includes 309551 records from 188 constituent datasets: 1 records from Données du/de la naturaliste BITSCH Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Dr Mary Gillham Archive Project. 3 records from Données ONF faune-flore-fonge. 36 records from Phenological Center - Birds (Arkhangelsk). 2 records from Bell Museum birds. 19 records from North East Scotland Birds (1883-2010). 53 records from Birds ringed with Norwegian rings 1961-1990. 1 records from CRBPO : STOC, Baguage. 1 records from Literature review of the Scheldt estuary with emphasis on the biotic components. 5 records from Geographically tagged INSDC sequences. 4 records from Bird Atlas 2007 - 2011. 24 records from Données du naturaliste Thierry Roy provenant de la base de donnée du SINP Île-de-France CETTIA. 55 records from Estonian Nature Observations Database. 53 records from Swedish Bird Survey: Summer point count routes (Sommarpunktrutterna). 1 records from Species recordings from the Danish National portal Arter.dk. 1 records from Anillamiento SEO_Bird ringing. 25 records from Upper Silesian Museum, Bird Observations. 9 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 1 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 66 records from Birds (GMBO-BI). 159 records from Finnish Winter Bird Census. 10 records from Bird collection NTNU University Museum. 144 records from Chronicle of Nature - Phenology of Birds of State Nature Reserve Malaya Sosva. 9380 records from DOF - Observations from the Danish Ornithological Society. 1 records from BIRDRACE - The famous Grouse feat. The James. 11 records from 2020_biodiversity_new_contents. 55 records from Observatoire LPO Franche-Comté des espèces (oiseaux, amphibiens, reptiles, mammifères sauf chauve-souris). 3 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 1 records from Collection Aves (bird skeletons) SMF. 1 records from NRW Regional Data: South East Wales Non-sensitive species. 9 records from National Trust Species Records. 827 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 2 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 1 records from BIRDRACE Raumpatrouille Oriolus. 13 records from RBINS DaRWIN. 2 records from DEMNA-DNE : Exotic animal occurrences in Wallonia, Belgium. 57 records from LERN Records. 172 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 3 records from Balsfjord Nature Reserves. 2 records from Miscellaneous records held on the Cofnod database. 53 records from Phenological Center - Birds (Laplandskiy). 1 records from SER Species-based Surveys. 259 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 25 records from CEN_PACA_2017_12_18. 6 records from natagora-earlybirds. 10 records from Bird records for Argyll for the years 2002 and 2003. 1 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 64 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 1 records from FNL e.V.. 4 records from RECORD Aves Data. 650 records from Oiseaux de France métropolitaine en hiver 1977-1981. 682 records from RU-BIRDS.RU, Birds observations database from Russia and neighboring regions. Zoological Museum of M.V. Lomonosov Moscow State University.. 3 records from Carnet B Lorraine. 1687 records from Observation.org, Nature data from around the World. 1 records from British bird eggs in the collections of World Museum, National Museums Liverpool. 1 records from Ghent University - Zoology Museum - Vertebrate collection. 2 records from Institut Mediterrani d'estudis Avançats (CSIC-UIB): IMEDEA-VERT. 389 records from Annual Census on Waterfowl (Anatidae) Population. 1 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7091 records from EOD - eBird Observation Dataset. 3 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from The Taiwan Breeding Bird Survey Data. 26 records from Museum of Comparative Zoology, Harvard University. 1 records from Annales de la Société Linnéenne de Maine-et-Loire. 1 records from Base de données faune - DREAL Centre-Val de Loire. Polygones. 1 records from UAM Bird Collection (Arctos). 51 records from 2020_biodiversity_information_observation. 414 records from Biologiezentrum Linz. 10767 records from Finnish Bird Ringing and Recovery Database. 3 records from Shropshire Ecological Data Network database. 1 records from BIRDRACE Cuxland - Schwenke Geo Consult. 13 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 2 records from Ornithologie Federsammlung - SNSD. 1 records from BoBO - Botanic Garden and Botanical Museum Berlin Observations. 1 records from BIRDRACE Linumer Luchschleicher. 14 records from TOV-E Bird monitoring sampling data. 1 records from Données de la structure Naturessonne provenant de la base de donnée du SINP Île-de-France CETTIA. 157 records from Naturalis Biodiversity Center (NL) - Aves. 9279 records from naturgucker. 1034 records from Watervogels - Wintering waterbirds in Flanders, Belgium. 15 records from Données faune pour le rapportage européen DHFF-DO 2018. 2 records from Abundance of birds on the channels of Lena Delta in the brood period. 8 records from Animal Sound Archive. 3 records from National System of Protected Areas in Poland - Animals. 8 records from 2019_nsmk_bi_20200324. 68 records from Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995. 894 records from iNaturalist Research-grade Observations. 13 records from Fife non-breeding bird 5km atlas 1991-99. 2 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 18 records from Merseyside BioBank (verified). 38 records from Biodiversitätsdatenbank Salzburg. 2 records from South East Scotland Tetrad Atlas 2007 - 2013 - non-sensitive winter species. 47 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 4 records from Abundance of birds in the Lena Delta Region. 2 records from BIRDRACE Havelland. 89 records from Waterbird census in Spain. 1 records from Finnish monitoring scheme of birds and mammals visiting bird feeders during winter. 417 records from Chinese Wild Bird Federation Bird Records Database. 22 records from Leicestershire and Rutland Environmental Records Centre records 2010-2014. 1 records from Birdrace-ARKONAuten-Rügen. 1 records from Norwegian Biodiversity Information Centre - Other datasets. 1 records from Long-term fauna and flora records of the experimental forests of the Forest Research Station of Hokkaido University, Japan. 203 records from Bird Ringing Centre in Sweden (NRM). 2673 records from EBCC Atlas of European Breeding Birds. 1 records from BIRDRACE Gätkes Erben. 3 records from Leicestershire and Rutland Environmental Records Centre records 2000-2009. 1878 records from Birds (KIEE-BI). 5 records from RNF - Données du Parc Naturel Régional de la Forêt d'Orient. 2 records from Highland bird data 2002 - 2003 - non-breeding records. 22 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 3 records from The atlas of breeding birds in Małopolska. 408 records from Comptages Wetlands, dénombrements des Oiseaux d'eau à la mi-janvier en France métropolitaine. 2 records from All taxa records for Leicestershire and Rutland. 4 records from My naturesounds - nature observations with sound recordings. 85 records from 2019_NSMK_BI. 3 records from Nigerian Conservation Foundation (NCF) Database of Birds from Nigeria. 1 records from Naturhistorisches Museum Mainz, Zoological Collection. 2 records from Macaulay Library Audio and Video Collection. 51 records from Réserve_Naturelle_de_Camargue_2017_12_18. 1 records from Données RNF - PNR des ballons des Vosges. 1 records from BIRDRACE HGON Kelkheim-Rumpfteam. 1 records from Chronicle of Nature - Phenology of Birds of Sikhote-Alin State Nature Biosphere Reserve Named After K. G. Abramov. 229394 records from Artportalen (Swedish Species Observation System). 1 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 15 records from Natural History Museum Rotterdam - Specimens. 3 records from National Trust for Scotland Species Records. 16393 records from Norwegian Species Observation Service. 113 records from Données des réserves naturelles nationales gérées par la Ligue pour la protection des oiseaux (LPO). 8369 records from Estonian Ornithological Society (BirdLife Estonia). 1 records from BIRDRACE Die Ziegeneier. 4 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 9 records from Isle of Wight Notable Species. 131 records from Birds of Northern Eurasia. 1 records from BIRDRACE Usedommeln. 2 records from Biodiversity4all Research-Grade Observations. 1 records from Field Museum of Natural History (Zoology) Bird Collection. 12 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 30 records from Azorean Biodiversity Portal. 3 records from Données naturalistes hors Île-de-France saisies dans Cettia-idf. 2 records from BioFokus. 10 records from Chronicle of Nature - Phenology of Birds of FGBU National Park Kenozersky. 27 records from North Merseyside Local Species Data (DEFRA Grant 23169). 96 records from Oiseaux de France métropolitaine 2009-2013 en période hivernale. 1 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 1 records from BUND - Dassower See (Lübeck/Dassow). 565 records from Long term data from the Hanko Bird Observatory. 26 records from Tour_du_Valat_2017_12_18. 2 records from Données naturalistes de Julien BIRARD. 16 records from SEAPOP - Last observation per locality in winter season. 89 records from Xeno-canto - Bird sounds from around the world. 833 records from Waarnemingen.be - Bird occurrences in Flanders and the Brussels Capital Region, Belgium. 80 records from WIWO (NL) - Monitoring and breeding ecology of arctic birds at Medusa Bay. 7 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 39 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 1 records from Sheffield Bird Study Group (Yorkshire records). 1 records from IPAE egg clutches collection (Aves). 76 records from Birds and Mammals Collections of the Zoological Museum of M.V. Lomonosov Moscow State University. 2 records from Données de l'Observatoire de la Faune de Bourgogne. 2 records from BRERC species records from all years at full resolution excluding Notable Species within the last 10 years. 2 records from Tullie House Museum Natural History Collections. 58 records from National Wetland Inventory (NV). 5 records from University of Michigan Museum of Zoology, Division of Birds. 857 records from Hatikka Observation Database. 2 records from Données naturalistes de Benoit FONTAINE. 34 records from ArtenFinder. 1 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 1 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 22 records from Collections and observation data National Museum of Natural History Luxembourg. 1 records from Data collected on citizen science web portal www.ornitho.cat. 126 records from Arctic Species Trend Index (ASTI) : Terrestrial. 151 records from Lund Museum of Zoology (MZLU). 2 records from Données faune Nature 18 - 2017. 76 records from Swedish Bird Survey: Fixed routes (Standardrutterna). 80 records from Données d'occurrences Espèces issues de l'inventaire des ZNIEFF. 11 records from SEWBReC Birds (South East Wales). 1 records from BIRDRACE Tick, Trick und Track. 5 records from Chronicle of Nature - Phenology of Birds of Kondinskie Lakes National Park named after L. F. Stashkevich. 4 records from Abundance of birds on the channels of Lena Delta in the fall migration period. 2 records from Birds ringed with Norwegian rings 1914-1960. 16 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2017.. 2 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 1 records from Irish Wetland Birds Survey (I-WeBS) 1994-2001.. 13 records from Royal Belgian Institute of Natural Sciences Bird collection. 780 records from NBIS Records to December 2016. 2 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 1 records from RNF - Données de l'association Vivarmor Nature. 11 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. 1 records from Birdrace-WeserEggeLäufer-Höxter. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences